Development and evaluation of a novel E7 multi-epitopic vaccine for human papillomavirus type 16: design, expression, purification, and immunological characterization - Bahareh Bahmani; Zahra Amini-bayat; Mohammad Mehdi Ranjbar; Masoud Hassanzadeh Makoui; Amir-Hassan Zarnani (BMC Infectious Diseases)
Abstract Background Persistent infection with high-risk Human papillomavirus (HPV), specifically HPV-16, is the leading cause of cervical cancer. Although preventative vaccines have shown significant efficacy in preventing HPV infection, cervical cancer is a significant public health issue that affects millions of women worldwide. Modern therapeutic approaches, such as peptide vaccines, could be promising and have potential for the treatment of the HPV-infected population. Methods A HPV16-E7 multi-epitopic vaccine (MEVE7) was designed to comprise potent CD4 + and CD8 + T cell epitopes and optimally expressed in a prokaryotic expression system. Polyclonal antibodies were generated, and their reactivity with immunizing antigen and native protein in E7 expressing cells (TC-1) was assessed by ELISA and immunofluorescent staining, respectively. The efficacy of the vaccine was assessed in a therapeutic animal model of HPV-induced cancer. Results Our study revealed that the final construct was successfully expressed in E. coli BL21 (DE3)-gold within 4 h of induction as inclusion bodies. Among the tested solubilization buffers, the buffer with a pH of 12 and containing 2 M urea showed the highest solubilization effect. Polyclonal antibodies directed against the E7 multi-epitope vaccine were able to react strongly with the immunizing antigen and E7-bearing cells (TC-1). Immunization of TC-1 tumor-bearing mice with HPV16-E7, markedly delayed tumor growth and propagation. Conclusion The poly-epitope vaccine for HPV16-E7, as expressed and purified in this research, is highly immunogenic and capable of triggering E7-specific antibodies, making it a potential therapeutic HPV vaccine. Further research is needed to optimize the vaccination schedule and assess the E7-specific immune cell profile.